Vitamin B6 resensitizes mcr-carrying Gram-negative bacteria to colistin - Tianqi Xu; Dan Fang; Fulei Li; Zhiqiang Wang; Yuan Liu (Communications Biology)
Abstract Antimicrobial resistance poses a severe threat to human health, with colistin serving as a critical medication in clinical trials against multidrug-resistant Gram-negative bacteria. However, the efficacy of colistin is increasingly compromised due to the rise of MCR-positive bacteria worldwide. Here, we reveal a notable metabolic disparity between mcr-positive and -negative bacteria through transcriptome and metabolomics analysis. Specifically, pyridoxal 5’-phosphate (PLP), the active form of vitamin B6, was significantly diminished in mcr-positive bacteria. Conversely, supplementing with PLP could reverse the metabolic profile of drug-resistant bacteria and effectively restore colistin’s bactericidal properties. Mechanistically, PLP was found to augment bacterial proton motive force by inhibiting the Kdp transport system, a bacterial K+ transport ATPase, thereby facilitating the binding of the positively charged colistin to the negatively charged bacterial membrane components. Furthermore, PLP supplementation triggers ferroptosis-like death by accumulating ferrous ions and inducing lipid peroxidation. These two modes of action collectively resensitize mcr-harboring Gram-negative bacteria to colistin therapy. Altogether, our study provides a novel metabolic-driven antibiotic sensitization strategy to tackle antibiotic resistance and identifies a potentially safe antibiotic synergist.